Modeling of non-ductile RC structure under near-fault ground motions: A nonlinear finite element analysis. Issue 9 (July 2022) - Hidayat, Banu A; Hu, Hsuan-Teh; Hsiao, Fu-Pei; Shen, Wen-Cheng; Weng, Pu-Wen; Han, Ay Lie; Chan, Li-Yin; Haryanto, Yanuar
The old existing reinforced concrete (RC) structures in Taiwan are susceptible to severe damage under earthquakes because of the soft-story mechanism. Moreover, the effects of near-fault ground motions often contain a long period of velocity pulse and permanent ground displacement. This study is based on the tri-axial shaking table test conducted at the National Center for Research on Earthquake Engineering in Taiwan and a series of seismic performance evaluations of a non-ductile RC structure in Taiwan. Finite element analysis (FEA) will be conducted to simulate the linear and nonlinear behavior of the seven-story building. This accommodates the damage plasticity model for concrete and the elastic-perfectly plastic model for reinforcement. Comparison of the results between the experimental test and numerical model showed that the similarity of the vibration period has a great influence on the simulation results. The findings showed that the data of acceleration and displacement behavior corresponded with the experimental results in a satisfactory margin. Also, the damage mode is very similar to the shaking table test results. The study found that using FEA can satisfactorily simulate the seismic performance of mid-rise buildings under a near-fault earthquake.